Improving Students’ Reading Comprehension by Using Problem-based Learning Strategy - Wandi Syahfutra; Siti Niah (Faculty of Teacher Training and Education, 2019)
Abstrak This study explores an improving students’ reading comprehension by using problem-based learning strategy by formulating quasi-experimental design of Darma Yudha Junior High School. Reading is one of subject that some of Indonesia students faced many difficulties to understand for some reasons. The strategy selection has an important role to create the expectation of the teachers that can be answered by the implementation of creative method, interested materials or enjoyable learning process. Problem-based learning (PBL) is one of strategy of expressing ideas to experience real life context to build critical thinking and problem solving skill. In problem-based learning, students work in collaborative groups to identify what they need to learn in order to solve a problem. The goals of problem-based learning include helping students develop; 1) flexible knowledge, 2) effective problem-solving skills, 3) effective collaboration skills, 4) life-wide learning and 5) intrinsic motivation. In other hand; PBL is well suited to helping students become active learners because it situates learning in real-world problems and makes students responsible for their learning. Based on the result of research, it is found that PBL is one of instructional strategy that offers potentials help to improve students’ reading comprehension and motivation. Keywords: reading comprehension, problem-based learning, and motivation.